PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT.CAHAYA KAWI ULTRAPOLYINTRANCO MEDAN - Cindy Setiani; Abd. Rasyid Syamsuri (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
The results of the study partially show that training (x1) has a positive and significant effect on employee performance (y) at PT. Cahaya Kawi Ultrapolyintraco Medan with a t-count value of 2.002 > ttable 1.660. Work motivation (x2) has a positive and significant effect on employee performance at PT. Cahaya Kawi Ultrapolyintraco Medan with a t value of 16,229 > t table 1,660. Simultaneously, the training variables (x1) and work motivation (x2) have a positive and significant effect on employee performance at PT. Cahaya Kawi Ultrapolyintransco Medan with a calculated F value of 144.47 > F table 3.09. Based on the value of the coefficient of determination R2, the effect of training and work motivation on employee performance has a value of 0.735 or 73.5%, while the remaining 26.5% is influenced by other variables not examined in this study